2020
DOI: 10.2139/ssrn.3683776
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Ethnic Minorities Changes Attitudes to Them

Abstract: Does exposure to ethnic minorities change the majority's attitudes towards them? We investigate this question using novel panel data on attitudes from a general-population sample in the Netherlands matched to geographical data on refugees. We find that people who live in neighborhoods of refugees for a sufficiently long time acquire a more positive attitude. Instead, people living in municipalities hosting refugees, but not in their close neighborhood, develop a more negative attitude. The positive neighborhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…They find suggestive evidence that voters worry about negative effects of immigration on labour markets and on the quality of their neighbourhood. Similarly, Albrecht et al (2020) examine whether exposure to ethnic minorities change the majority's attitudes towards them, by looking specifically at the relationship between the location of asylum reception centres in the Netherlands and panel data on local attitudes towards ethnic diversity. They find that locals who live in the close neighbourhood of a refugee centre develop a more positive attitude towards ethnic diversity, in particular if exposure lasts at least six months, while people living in municipalities that host refugees, but not in their close neighbourhood, develop a more negative attitude.…”
Section: Theoretical Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…They find suggestive evidence that voters worry about negative effects of immigration on labour markets and on the quality of their neighbourhood. Similarly, Albrecht et al (2020) examine whether exposure to ethnic minorities change the majority's attitudes towards them, by looking specifically at the relationship between the location of asylum reception centres in the Netherlands and panel data on local attitudes towards ethnic diversity. They find that locals who live in the close neighbourhood of a refugee centre develop a more positive attitude towards ethnic diversity, in particular if exposure lasts at least six months, while people living in municipalities that host refugees, but not in their close neighbourhood, develop a more negative attitude.…”
Section: Theoretical Motivationmentioning
confidence: 99%
“…Meanwhile, the literature that tests the 'contact hypothesis' in relation to refugees and host populations is mostly limited to a few studies that focus on the impact of sudden refugee flows in European countries on public attitudes and support for right-wing parties. While most of these studies find that contact (or short-term 'exposure') has negative effects on host attitudes towards refugees (Halla et al 2017;Dinas et al 2019;Ajzenman et al 2020;Rozo and Urbina 2020;Rozo and Vargas 2021), some find no effect (Hennig 2021) or heterogeneous effects that vary with the intensity of exposure (Albrecht et al 2020;Steinmayr 2021) and differ in urban versus rural contexts (Dustmann et al 2019). The broader literature on 'native' attitudes towards immigration also focuses almost exclusively on Europe and North America and reaches mixed conclusions (Hopkins 2010;Hainmueller and Hopkins 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Laurence and colleagues (2019) found that communities that are racially diverse and segregated exhibited elevated prejudice, while communities that are racially diverse and integrated exhibited stable, or somewhat improving, intergroup relations. The negative effect within segregated communities was driven by both lower positive intergroup contact and higher perceived threat (Laurence et al, 2019; see also Albrecht et al, 2020;Rocha & Espino, 2009;Zingher & Steen Thomas, 2014). Taken together, these studies combine to suggest that the benefits of incidental intergroup contact are both direct and indirect and can go a long way in encouraging "members of advantaged racial groups to become psychologically invested in the perspectives, experiences, and welfare of members of disadvantaged racial groups" (Tropp & Barlow, 2018, pg.…”
Section: Whites' Structural Preferences Results In Less Incidental Intmentioning
confidence: 99%
“…Moreover, while transient refugee exposure increases far-right voting, persistent or meaningful contact appears to reduce anti-immigration sentiment (e.g. Steinmayr, 2021;Dinas et al, 2019;Albrecht et al, 2020;Bursztyn et al, 2021;Asimovic et al, 2022). 4 We complement this literature on refugee immigration in two ways.…”
Section: Introductionmentioning
confidence: 99%